Ocular Complications of Measles; A Case Series - Arshad Shaikh, Erum Shahid, Uzma Fasih (Pakistan Journal of Ophthalmology, 2017)
Purpose: To report case series of ocular complication in patients with measles and how to manage them. Study Design: Case series Place and Duration of Study: Abbasi Shaheed Hospital, Karachi. Winter Spring outbreak (January – April) 2016. Material and Method: This is a case series of 9 patients who presented in an eye OPD with ocular complications of measles over a period of 2 months during spring break 2016. Their ages range between 7 months to 21-year-old. 7 patients presented with kerato conjunctivitis, 1 with keratomalacia and 1 with preseptal abscess. Result: All the patients with keratoconjunctivitis responded to treatment and were 6/6. A seven-month old infant had keratomalacia and ended with leucoma in one eye. Another 1-year-old girl with preseptal cellulitis was treated with incision and drainage. Conclusion: Keratitis is a common complication of measles which may lead to a serious complication like keratomalacia. Preseptal abscess is another rare complication to look out for. Key words: Measles, ocular complications, keratoconjunctivitis, keratomalacia